1990
DOI: 10.1210/endo-127-1-191
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin Decreases Thyrotropin-Releasing Hormone-Stimulated Prolactin Release through a Mechanism That Involves Inhibition of Inositol Phosphate Production*

Abstract: Calcitonin is present in both the hypothalamus and pituitary of the rat, and normal rat anterior pituitary cells express calcitonin receptors. Calcitonin has been reported to inhibit or to stimulate PRL release from rat anterior pituitary cells. We have investigated the effects of salmon calcitonin on basal and stimulated PRL release from rat anterior pituitary cells and have studied the effects of this peptide on the intracellular biochemical pathways involved in PRL release. Salmon calcitonin had no signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…Similarly, our studies suggest that CT inhibits PRL release and PRL gene transcription, and also attenuates thyrotropin-releasing hormone (TRH)-and suckling-induced PRL release and synthesis (Shah et al 1988, Judd et al 1990. CT is also a potent inhibitor of lactotrope proliferation (Shah et al 1999).…”
Section: Gct1-asct-absupporting
confidence: 57%
See 1 more Smart Citation
“…Similarly, our studies suggest that CT inhibits PRL release and PRL gene transcription, and also attenuates thyrotropin-releasing hormone (TRH)-and suckling-induced PRL release and synthesis (Shah et al 1988, Judd et al 1990. CT is also a potent inhibitor of lactotrope proliferation (Shah et al 1999).…”
Section: Gct1-asct-absupporting
confidence: 57%
“…Previous evidence has shown that SCT, when administered either centrally or peripherally, inhibits PRL release in rats (Olgiati et al 1981(Olgiati et al , 1982(Olgiati et al , 1983. In vitro experiments from this and other laboratories have extended these earlier findings by demonstrating that SCT acts directly at the level of lactotropes to inhibit PRL release, PRL gene transcription and lactotrope cell proliferation (Shah et al 1988, 1999, Judd et al 1990, Sortino et al 1991, Zhang et al 1995. A role for the endogenous peptide in these processes is demonstrated by the findings that immunoneutralization of pit-CT with GCT1 anti-SCT serum causes a significant increase in PRL release from cultured AP cells as well as in ovariectomized conscious rats (Shah et al 1993.…”
Section: Gct1-asct-abmentioning
confidence: 53%
“…It has also been implicated in the regulation of several functions in reproductive and neuroendocrine tissues (31)(32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…In particular sCT has been shown to be a potent inhibitor of GH secretion in both humans [12]and rats [13]and is considered, at least under certain conditions, as a physiological PRL-inhibiting factor [14, 15]. …”
Section: Introductionmentioning
confidence: 99%